2005
DOI: 10.1111/j.1365-3059.2005.01223.x
|View full text |Cite
|
Sign up to set email alerts
|

Discovery of the Eucalyptus canker pathogen Chrysoporthe cubensis on native Miconia (Melastomataceae) in Colombia

Abstract: Chrysoporthe cubensis is one of the most serious canker pathogens on commercially grown Eucalyptus species in the tropics and subtropics. During recent surveys for native hosts of C. cubensis in Colombia, fungi with fruiting structures similar to those of C. cubensis were found on native Miconia theaezans and Miconia rubiginosa, both members of the Melastomataceae. These fungi were identified based on morphology and DNA sequences of the ITS1/ITS2 region of the rDNA operon and the β‐tubulin genes. The majority … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
35
0
5

Year Published

2009
2009
2022
2022

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 54 publications
(49 citation statements)
references
References 26 publications
(58 reference statements)
2
35
0
5
Order By: Relevance
“…Following inoculation, Chr. austroafricana from South Africa was shown to be the most pathogenic species (Roux et al 2003;Wingfield 2003;Rodas et al 2005;Gryzenhout et al 2005). Results of the present study have, however, shown that Chr.…”
Section: Discussionmentioning
confidence: 99%
“…Following inoculation, Chr. austroafricana from South Africa was shown to be the most pathogenic species (Roux et al 2003;Wingfield 2003;Rodas et al 2005;Gryzenhout et al 2005). Results of the present study have, however, shown that Chr.…”
Section: Discussionmentioning
confidence: 99%
“…Eucalyptus where these trees are grown as exotics (Coutinho et al 2011;Glen et al 2007;Rodas et al 2005) , there are far fewer examples of movement of apparently introduced Eucalyptus pathogens to native plants (Crous and Groenewald, 2005). Results of this study provide important new information that this movement is far more common than has been previously thought.…”
Section: While There Are Growing Numbers Of Examples Of Pathogens Of mentioning
confidence: 79%
“…This rust disease is native on Myrtaceae in South and Central America and has adapted to infect Eucalyptus in that region (Coutinho et al 1998, Glen et al 2007). In addition, there are many recent examples of members of the Cryphonectriaceae, that are native on members of the Myrtales, adapted to infect Eucalyptus in Africa (Heath et al 2006) as well as South and Central America and Asia Hodges et al 1986;Myburg et al 2003;Rodas et al 2005). …”
Section: A Diverse Group Of Mycosphaerellaceae and Teratosphaeriaceaementioning
confidence: 99%
“…However, attempts to isolate these fungi as endophytes by Vermeulen et al (2011) were not successful. This might be explained by the fact that isolations on agar could have been overgrown by more rapidly developing fungi such as for example the Botryosphaeriaceae, which are common endophytes in Angiosperm trees including the Myrtales (Pavlic et al 2007;Roux et al 2000Roux et al , 2001Smith et al 1996b;Slippers and Wingfield 2007 (Gryzenhout et al 2004;Rodas et al 2005;Wingfield et al 2001). Thus, placing branch samples with considerable surface area into moistened florist foam, allowing the samples to dry out slowly over a number of months, stimulated the Cryhonectriaceae present to develop and sporulate.…”
Section: Discussionmentioning
confidence: 99%
“…Host genera include Lagerstroemia , Miconia (Rodas et al 2005), Psidium (Hodges 1988), Syzygium (Hodges et al 1986), Tibouchina ) and a number of others (Barreto et al 2006;Gryzenhout et al 2006;Seixas et al 2004). In most countries where Eucalyptus species are grown as non-natives, they occur in close proximity to related, native plants in the Myrtales (Seixas et al 2004;Wingfield et al 2001).…”
Section: Introductionmentioning
confidence: 99%